Occurrence of Natural Enemies of Phytophagous Mites on Grapevine Leaves Following. Application of Fungicides for Disease Control - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
A field trial was conducted in a Cape Riesling vineyard to evaluate the effect of different fungicides in a programme for the control of powdery mildew, Uncinula necator (Schw.). A post-harvest assessment indicated the presence of a diverse group of predators, with Amblyseius addoensis Van der Merwe & Ryke, the most abundant in all treatments.